An Approach to the Defining Factors of Salaries in the Spanish Tourist Sector. - Sánchez-Cubo, Francisco; Mondéjar-Jiménez, José; García-Pozo, Alejandro (Emerald, 2023)
Purpose: The importance of workers in labour-intensive industries, such as tourism, is undeniable. In this sense, it has been investigated for decades from various methodological approaches. However, in the academic literature on tourism, the PLSSEM path modelling technique has hardly been used. Methodology: Therefore, this work uses that technique to contrast which factors define the employees' wages in the Spanish tourism industry. Additionally, an IPMA analysis is carried out, which provides informed decision-making. Findings: Thus, the main results obtained are the verification and measurement of the relationships of Human Capital, Labour Conditions and Market with Wages, and the relation between Human Capital and Labour Conditions. Besides, the improvement points in each variable are identified. Especial emphasis is given to those related to Human Capital and, partially, to the Market. Originality: Considering the turning point that the temporary cessation of the tourism industry activity due to the COVID-19 pandemic has been, it is essential to take advantage of it to identify and correct existing deficiencies. Therefore, this work aims to be a base document for the identification of these problems. Research limitations: However, there are certain limitations to this study. Mainly, as the indicators used are given by the 2018 Salary Structure Survey, they are stiff, and so the design of the model turns to be more difficult.
https://openpolicyfinder.jisc.ac.uk/id/publication/23862
Keywords: Turismo - España; Hostelería; Condiciones de trabajo; Recursos humanos; Salarios; Human Capital; Labour Conditions; Spain; Hospitality; Wages; Tourism